Developing the Readiness and Success Model of Information System Implementation in the Indonesian Equestrian Industry - Sopandi, Ajang; Yahaya, Nor Adnan; Subiyakto, Aang (Journal of Applied Data Sciences, 2024)
This study reports on the incorporation of technology readiness models in information system (IS) success models in the context of assessing readiness factors and the success of information system integration in the equestrian sports industry in Indonesia. As found in several information systems studies, many IS models are developed by adopting, combining, and adapting previous models. Researchers developed this model based on input-process-output logic and processional and causal models of information system success models. The developed model is structured by involving 12 variables and 62 indicators. The path of influence between variables is described by 30 links. In the research implementation stage, the model is also broken down into more detailed assessment instruments. Although these model development studies may have limitations on the assumptions used and the researchers' understanding, they can make theoretical contributions, particularly in terms of proposed new models. In addition, transparency in model development, proposed models, and data collection instruments may also be a practical consideration for advanced research in the context of readiness and successful implementation of information systems in the equestrian sports industry in Indonesia